(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mycoflora was isolated using soil dilution and soil plate method on Potato Dextrose Agar medium with the addition of the appropriate antibiotic, namely streptomycin. To help identify and describe the mycoflora, fungal guides were consulted. In the soil sample, Fusarium, Rhizopus, and Aspergillus were the most common fungus. They were successful in determining that Aspergillus niger was the species that was most common. Aspergillus niger was recognized based on its physical and biochemical characteristics, including conformation as shown by lactophenol cotton blue staining and microscopy.